2009
DOI: 10.1212/wnl.0b013e3181a92b13
|View full text |Cite
|
Sign up to set email alerts
|

MULTIPLE DURAL LESIONS MIMICKING MENINGIOMAS IN PATIENTS WITH CCM3/PDCD10 MUTATIONS

Abstract: MULTIPLE DURAL LESIONS MIMICKING MENINGIOMAS IN PATIENTS WITH CCM3/ PDCD10 MUTATIONSCerebral cavernous malformations (CCM) are in most cases located within the brain parenchyma. Familial forms of CCM (FCCM) are characterized by an autosomal dominant pattern of inheritance and the presence of multiple cerebral lesions. 1 Three CCM genes have been identified: CCM1/KRIT1, CCM2/MGC4607, and CCM3/PDCD10. 1,2 They are involved in 53%, 15%, and 10% of patients with FCCM. 3 All mutations lead to premature stop codons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…In a previous study on 333 CCM mutation carriers including 28 CCM3 patients belonging to 17 families, we suggested that the proportion of CCM3 patients with a childhood onset was higher compared to CCM1 and CCM2 patients [Denier et al, 2006]. We also showed in 4 unrelated CCM3 patients the occurrence of multiple dural-based lesions; however, the pathological nature of these lesions was unknown since none of these patients had undergone neurosurgery [Labauge et al, 2009].…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In a previous study on 333 CCM mutation carriers including 28 CCM3 patients belonging to 17 families, we suggested that the proportion of CCM3 patients with a childhood onset was higher compared to CCM1 and CCM2 patients [Denier et al, 2006]. We also showed in 4 unrelated CCM3 patients the occurrence of multiple dural-based lesions; however, the pathological nature of these lesions was unknown since none of these patients had undergone neurosurgery [Labauge et al, 2009].…”
mentioning
confidence: 64%
“…Our study group was composed of these 54 probands and 22 of their mutated relatives. Partial information on some of these patients have been previously reported [Denier et al, 2006;Ahdab et al, 2008;Labauge et al, 2009;Choe et al, 2010].…”
Section: Methodsmentioning
confidence: 99%
“…Early onset fulminant cerebral haemorrhage has previously been reported in patients with CCM3 mutations and seems to be more prevalent in this subgroup than in CCM1 or CCM2 mutation carriers [2,3]. A subset of CCM3 mutation carriers has been identified which has both, parenchymal CCM and dural-based lesions which show typical MRI features of meningiomas [4][5][6]. Previous histological studies in patients with mainly solitary dural-based MRI lesions showed that these lesions are cavernous angiomas [7].…”
Section: Discussionmentioning
confidence: 99%
“…84 Multiple meningiomas have been observed in patients with mutations in CCM3/PDCD10, a gene associated with cerebral cavernous malformations that contributes to proliferation and resistance to apoptosis via activation of AKT signaling, 20,48,56,75 and the SUFU gene, which regulates hedgehog signaling.…”
Section: Other Germline Syndromesmentioning
confidence: 99%